The Interconnectedness Of Nature And The Human Being In The Scientific Heritage Of Abu Rayhan Beruni: A Socio-Philosophical Analysis (The Peerian Journal, 2025)
This article presents a comprehensive analysis of the concept of the interconnectedness between the human being and nature in the scientific and philosophical heritage of Abu Rayhan Muhammad ibn Ahmad al-Biruni. The study explores al-Biruni’s theoretical views grounded in the laws of nature, his understanding of the human being’s place within the natural environment, and the reciprocal relationship between human practical activity and natural processes as reflected throughout his works. Furthermore, the article examines the scientific research methods proposed by al-Biruni, highlighting the significance of empirical observation and experimentation in the acquisition of knowledge about nature, as well as the socio-philosophical implications of his ideas concerning the human–world relationship. The relevance of al-Biruni’s intellectual legacy in contemporary ecological and humanistic contexts is also discussed, emphasizing the theoretical importance of his insights for fostering a balanced and harmonious relationship between humans and the natural world.